"More Enduring Structures": The Oil Industry's Effects on the Social and Economic Transformation of Pennsylvania's Oil Region, 1850-1865 - Varee, Nolan (My University, 2023)
This study examines the social and economic changes that occurred throughout Pennsylvania?s oil region following the introduction of the commercial oil industry in 1859. By connecting the history of the oil industry to the development of local towns within the region where it began, this study fills a gap in the understanding of the industry?s effects on rural communities in the late nineteenth century. By highlighting the involvement of locals who understood the capabilities of oil far beyond what previous scholars have given them credit for, this study argues that social and economic networks flourished prior to the development of the oil industry. The rapid developments in the social and economic structures of the region which took place following the introduction of the oil industry are also discussed in length.
Keywords: Drake's well; Oil; Oil City; Pennsylvania Oil Region; Petroleum; Titusville